Development of basic provisions of the marketing policy of a travel agency - Necheporenko, Denis; Kramskoy, Oleksandr; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
The purpose of tourism marketing is to serve and satisfy the needs of tourist customers. From this point of view, marketing should serve a clear purpose: how to function successfully. Terms of application of marketing in tourism: deep saturation of the market with tourist services; competition between travel industry agencies; free market relations; freelance work of travel agencies
Розробка базових положень маркетингової політики туристичного агентства
Keywords: business; competitiveness; tourism market; tourism industry